Influence of virtual CSR gamification design elements on customers’ continuance intention of participating in social value co-creation: The mediation effect of psychological benefit - Jun, Fan; Jiao, Juanni; Lin, Philip (Asia Pacific journal of marketing and logistics, 2020)
PurposeThe purpose of this paper is to investigate the effect of gamification design elements of virtual corporate social responsibility (CSR) game on customers’ continuance intention to participate in social value co-creation and the mediation effect of psychological benefit.Design/methodology/approachThree scenario simulation experiments of the between-subjects design were conducted to examine the influencing mechanism of reward mechanism of virtual CSR game on customers’ continuance intention to participate in social value co-creation.FindingsThe findings indicated that: there are significant differences between the effect of behavior-based reward and result-based reward on customers’ continuance intention to participate in social value co-creation; the psychological benefit plays a moderating role between game reward mechanism and customers’ intention to continuously participate in social value co-creation; the game narrative mode plays a moderating role in the influence of game reward mechanism on customers’ intention to continuously participate in social value co-creation; the background for game placement moderates the interactions of game narrative mode and game reward mechanism on customers’ continuance intention to participate in social value co-creation, namely there is significant interaction of gamification design elements on psychological benefit and customers’ continuance intention to participate in social value co-creation.Research limitations/implicationsThis research has the following limitations. First, restricted by research conditions, the game scene, as the experiment material, can only be exposed to the participants in the form of text, thus customers’ psychological benefit (especially the entertainment experience) may be affected. Second, theoretical argument and literature support were not enough when the authors put forward the research hypotheses, due to the lack of research on the application of gamification in the CSR field. Third, considering the complexity, the authors took the psychological benefit as a unidimensional variable, in this research; it may be funnier to divide it into three variables. Finally, because the game design elements form into a virtual customer environment that jointly influences customers’ psychological benefit, the method of qualitative comparative analysis can be considered in future research.Practical implicationsIt provides insights for marketers on the planning and design of a CSR strategy. The conclusions of this research have a certain guiding significance to the formulation of CSR strategy and the practice of social value co-creation. First, enterprises can apply gamification to the design of virtual CSR projects to promote customers’ continuance intention to participate in social value co-creation. Second, on the consideration of customers’ psychological benefit, enterprises should reasonably match such game design elements as game placement background, game narrative mode and game reward mechanism, when designing a virtual CSR game, so as to promote customers continuously participating in a virtual CSR project.Social implicationsVirtual CSR projects are in fact the activities that enterprise co-create social value with their stakeholders. So, the research on customers’ continuous participation in virtual CSR projects is helpful for increasing social welfare.Originality/valueThis study confirms the effect of reward mechanism of a virtual CSR game on customers’ continuance intention to participate in social value co-creation from the perspective of customer psychological benefit. It also provides insights for marketers on the planning and design of a CSR strategy.